Ln(7x-1)=3

Simple and best practice solution for Ln(7x-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(7x-1)=3 equation:


Simplifying
Ln(7x + -1) = 3

Reorder the terms:
nL(-1 + 7x) = 3
(-1 * nL + 7x * nL) = 3
(-1nL + 7nxL) = 3

Solving
-1nL + 7nxL = 3

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Reorder the terms:
-3 + -1nL + 7nxL = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + -1nL + 7nxL = 0

The solution to this equation could not be determined.

See similar equations:

| 5x^2-9=11 | | 3x+2=10x+12 | | -4x+18=-6(3x-3) | | y=32x+25 | | 4(3-u)=-4u-12 | | 10x+4y+5z-5x+2z-7y= | | x+y+z=-7 | | f(x)=5x^2-10x+6 | | 5x^2-3x+18=5x^2+7x-12 | | x-9=2(x-1) | | 3/5x+4/9=10/3 | | 3x/4+2/3=2 | | 3x/4+2/3= | | 5x^2-1x-12=0 | | 3=1.7x | | 5x-3(x-4)=-2+5x-1 | | 0.75(5x-4)=0.5(4x+3) | | 2(x+2)+2(x+4)=26 | | 53c-23=23s | | 4x=5+5x | | 6(4s+3)=114 | | 1+x+3=5 | | 18-x=6 | | 8(2l+4)=192 | | 1+3(5)= | | -252=6v+6(-6+5v) | | f(x)=0.5(4)x | | 4(8+3k)=116 | | x+(2x+4)=7 | | 5(x+2)=7(x) | | -4(3+4n)=-140 | | ln(4x^2-20x+24)= |

Equations solver categories